Prognostic Value of Systemic Inflammation, Nutritional Status and Sarcopenia in Patients With Amyotrophic Lateral Sclerosis - Yahui Zhu; Ying Zhang; Mao Li; Jiongming Bai; Hongfen Wang; Xinyuan Pang; Rongrong Du; Jiao Wang; Xusheng Huang (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Nutritional status, systemic inflammatory responses and muscle mass are associated with the prognosis of patients with amyotrophic lateral sclerosis (ALS). However, the optimal biomarker for predicting prognosis remains unclear. This study aimed to identify the optimal indicators of survival among the nutrition‐based, inflammation‐based and muscle mass–related markers for ALS patients. Methods We enrolled ALS patients from January 2014 to December 2019. Experienced neurologists followed up with the participants until January 2022. This study included a total of 17 nutritional, systemic inflammatory or muscle mass–related indicators. Maximally selected rank statistics determined the cut‐off points for these indicators. Kaplan–Meier estimation was used to assess survival. Uni‐ and multivariate Cox proportional hazards models were used to determine the effects of indicators on survival. Finally, time‐dependent receiver operating characteristic (time‐ROC) curves and the C‐index were calculated to evaluate the predictive efficacy of different indicators. Results A total of 506 patients with ALS were enrolled in this study, including 288 males (56.9%) and 218 females (43.1%), with a mean age of 54.2 ± 10.5 years. Among these ALS patients, 334 cases (68.0%) either died or underwent tracheotomy. In univariate Cox proportional hazards regression, 11 indicators were significantly associated with ALS survival (p < 0.05). And systemic immune inflammation (SII), platelet‐to‐lymphocyte ratio (PLR), modified geriatric nutritional risk index (mGNRI), creatinine and sarcopenia index (SI, (creatinine/cystatin C) × 100) were determined as independent predictors (p < 0.05) in multivariate Cox proportional hazards regression. A higher SI predicted longer survival (hazard ratio, 0.59; 95% confidence interval [CI], 0.46–0.76; p < 0.001). The results of time‐ROC and C‐index analyses indicated that SI had the best predictive efficacy for ALS survival, with a C‐index of 0.65 (95% CI, 0.54–0.75) for 1‐year, 0.61 (95% CI, 0.57–0.65) for 3‐year and 0.59 (95% CI, 0.55–0.62) for 5‐year survival. Across different subgroups, SI had the highest C‐index in men and women, limb onset and aged < 60 year ALS patients, compared with other indicators. However, cystatin C was the best indicator for predicting the survival of ALS patients with bulbar onset, whereas the prognostic nutritional index (PNI) was the best for those aged ≥60 years. Conclusions The serum SI demonstrates superior prognostic ability compared to other inflammation‐based, nutrition‐based and muscle mass–related indicators for patients with ALS. Given its simplicity and availability, it is well suited for clinical use in evaluating the prognosis of ALS patients.